The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1210/endo-97-3-718
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Steroid and Gonadotropin Release Resulting from Surgical Stress During the Morning of Proestrus in 5-Day Cyclic Rats

Abstract: The purpose of this experiment was to determine whether surgical stress on the morning of proestrus would elicit an early release of gonadotropin from the pituitary. Animals exhibiting 5-day estrous cycles underwent bilateral sham-ovariectomy under ether anesthesia at 0800 h of proestrus. These animals had high levels of progesterone and estradiol following the surgery. These steroids were thought to be adrenal in origin, since animals adrenalectomized at 0800 h of proestrus had low progesterone levels and est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
1

Year Published

1977
1977
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 1 publication
1
20
1
Order By: Relevance
“…The high P4 concentration and low GnRH as a result of metritis might be responsible for ovarian quiescence. However, Nequin et al [14] reported that E2 concentration also increased in addition to P 4 concentration under a surgical stress condition, although this was not observed in this study.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The high P4 concentration and low GnRH as a result of metritis might be responsible for ovarian quiescence. However, Nequin et al [14] reported that E2 concentration also increased in addition to P 4 concentration under a surgical stress condition, although this was not observed in this study.…”
Section: Discussioncontrasting
confidence: 82%
“…This shows that the lifespan of the corpus luteum was not prolonged and that pseudopregnancy was not induced. Alternatively, stress stimulates progesterone secretion from the adrenal cortex in rats [7,14] and this secretion depends on corticotrophin releasing hormone (CRH) from the hypothalamus [22] . CRH also acted on cells directly producing GnRH and suppressed secretion of GnRH [9,13].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has indicated that control of pituitary secretion of follicle stimulating hormone (FSH, follitropin) may differ from that of pituitary secretion of luteinizing hormone (LH, lutropin) (1)(2)(3)(4)(5), in spite of the failure to find more than one hypothalamic decapeptide releasing factor acting on the pituitary-LH/FSH-RF (6). FSH is secreted in high amounts without LH, beginning [5][6][7][8][9][10][11][12] hr after ovariectomy in the rat (3,4) or following hypothalamic electrochemical stimulation in the specific locus (5).…”
mentioning
confidence: 99%
“…FSH is secreted in high amounts without LH, beginning [5][6][7][8][9][10][11][12] hr after ovariectomy in the rat (3,4) or following hypothalamic electrochemical stimulation in the specific locus (5).…”
mentioning
confidence: 99%
“…Although there were no significant differences between the group that underwent ECS at 13.00 h and the controls, there was an ap parent reduction in the mean ova per rat in this group. This could be due to the possibility that some of the rats in this group may have not fully recovered from the stressful ef- fects of stereotaxic surgery by the time that the critical peri od started (14.00h) and this may have had an effect on the preovulatory LH surge and ovulation [18,29]. Only when bilateral ECS was followed by the procedure for blood sam pling from the external jugular vein under ether anesthesia were the LH surge and ovulation significantly inhibited (ta ble II, fig-2).…”
Section: Discussionmentioning
confidence: 99%